Spillovers from China : Financial Channels - Mwase, Nkunde (Spillover Notes; Spillover Notes ;, 2016)
Although China's much-needed transition to a new growth path is proceeding broadly as expected, the transition is still fraught with uncertainty, including regarding the Chinese authorities' ability to achieve a smooth rebalancing of growth and the extent of the attendant slowdown in activity. Thus, in the short run, the transition process is likely to entail significant spillovers through trade and commodities, and possibly financial channels. This note sheds some light on the size and nature of financial spillovers from China by looking at the impact of developments in China on global financial markets, with a particular emphasis on differentiation across asset classes and markets. The note shows that economic and financial developments in China have a significant impact on global financial markets, but these effects reflect primarily the central role the country plays in goods trade and commodity markets, rather than China's financial integration in global markets and the direct financial linkages it has with other countries.